Industrial Water Waste, Problems and the Solution - Anna, Alif Noor (Forum Geografi, 1990)
Recently, the long term development in Indonesia has changed agricultural sector to the industrial sector. This development can apparently harm our own people. This is due to the waste that is produced from factories. The waste from various factories seems to have different characteristics. This defference encourages us to be able to find out different of methods of managing waste so that cost can be reduced, especially in water treatment. In order that industrial development and environmental preservation can run together in balance, many institutions involved should be consider, especially in the industrial chain, the environment, and human resource, these three elements can be examined in terms of their tolerance to waste.